Respuestas

2013-05-12T05:08:07+02:00

La ecuacion y + 10 = -5 (29 - y ) - 5 se resuelve de la siguiente manera:

                  y + 10 = -145 + 5y - 5 

                  y - 5y = -145 - 5 - 10

                  -4y     =  - 160

                    y     = -160 / -4

                    y     = 40

 

 

2013-05-12T06:05:22+02:00

y+10=-5(29-y)-5

y+10=-145+5y-5

y-5y=-145-5-10

   -4y=-160

       y=-160/-4

       y=40

 

 

(y+5)(y-2)+12=(x+2)-10

  2y-2y+5y-10=x+2-10

                    5y=x+2-10+10

                      y=x+2/5

 

 

Espero te sirva :D